Binding Study of Berenil and d(CGCGAATTCGCG)\(_2\) and d(CGCAAATTTGCG)\(_2\) DNA Dodecamers by Isothermal Titration Calorimetry and Molecular Docking Simulations - Rocha, Ramon Kleber da; Martins-José, Andrelly; Almeida, Vera Lucia de; Denadai, Ângelo M. L.; Lopes, Julio Cesar Dias (Recent Developments in Chemistry and Biochemistry Research Vol. 9, 2024)
Aims: Berenil, an anti-trypanosomal agent, is a dicationic bis-benzamidine classified as a minor groove binding ligand in AT-rich regions of DNA. However, previous studies have suggested that berenil can bind to various DNA double strands, exhibiting both intercalative and minor groove binding modes. Methods: This work presents a biophysical study using Isothermal Titration Calorimetry (ITC) and molecular docking simulations to investigate the interaction between berenil and synthetic DNA dodecamers d(CGCGAATTCGCG)2 (A2T2) and d(CGCAAATTTGCG)2 (A3T3). Wiseman Isotherm and classical thermodynamic equations were used to obtain the calorimetric data at 298 K. Results: ITC experiments and Autodock calculations provide thermodynamic parameters for berenil and DNA dodecamers complexation. Our results suggest that berenil shows a mixed bind behavior when binding to double-stranded DNA. It is possible that more than one berenil molecule can bind to DNA dodecamers' double strands. The second molecule may be interacting through intercalation binding mode. Conclusion: This study improves our understanding of the complex interactions between small ligands, like berenil, and DNA. The results show that the intercalative effect of the molecule is entropically driven. These findings could benefit the pharmaceutical development of antiprotozoal drugs in the future.